Perioperative and Pathological Outcome of Laparoscopic Radical Nephrectomy for Renal Cell Carcinoma (RCC) - Faruque, Mohammad Salahuddin; Alam, AKM Khurshidul (Sir Salimullah Medical College Journal, 2023)
Introduction: Laparoscopy has become a well-accepted technique to treat malignant renal conditions. For renal cell carcinoma laparoscopic radical nephrectomy is the treatment of choice in selected patients. Objective: To see the feasibility, perioerative and pathological outcome of laparoscopic radical nephrectomy (LRN) in different size of tumour in renal cell carcinoma (RCC). Materials and methods: A prospective analysis was performed in 29 patients who underwent laparoscopic radical nephrectomy for RCC between October 2017 and September 2019. Patients age, tumor size, co-morbidity index, operating time, duration of hospitalization, complications and pathology were recorded. Results: Nineteen male and ten female patients were treated laparoscopically and conversion to open surgery was not required in any case. The age ranged from 30 to 72 years, tumor size varied from 5 to 15 cm and one patient had left renal vein thrombus. The operative time ranged from 60 to 180 minutes and blood loss was 50 to 150 mL. Nine patients required blood transfusion. Ileus developed in 3 patients, port site infection in 4 patients, fever in 2 patients and respiratory insufficiency in another two patients post operatively which was treated accordingly. There was no major complications and surgery related mortality. Pathological outcome was recorded after getting histopathology reports. Conclusion: The laparoscopic radical nephrectomy for RCC is safe and oncologically sound. It may be done in large tumour also. The process constitutes minimal invasiveness, low death rates, minimal intraoperative blood loss and fast rehabilitation of the patients. Different pathological sub type may predict future outcome. Sir Salimullah Med Coll J 2023; 31: 112-115